Gastric Cancer Associated Risk Factors and Prevalence in Pakistan - Areeba Yousaf; Nerum Tasneem; Aqsa Mustafa; Ramsh Fatima; N. Nabia; Raza Ahmad Khan; Hafiz Abdulbasit; Muhammad Abubakar; A. Asadullah; Rana Rizwan; B. Baqa-ur-Rehman (ASEAN Journal of Science and Engineering, 2021)
Gastric cancer (GC) is the most lethal disease of all cancer types. In the last three decades, it has become the most common reason for death among all cancer types. Gastric cancer is at the fourth number in all over the world and annually 8,00,000 deaths are reported. Female gastric cancer has been increased in the last 5 years. Unexpected diversity has been noted in GC spreaders in the whole world. Eastern Europe, China, and South America are the major regions of Gastric cancer prevalence. Its main sources are correlated with 2 agents, dietary intake and Helicobacter pylori infection. Although in south Asia occurrence of H. Pylori is high but less prevalence risk. The sole methods to minimize the prevalence of gastric cancer include elimination of Pylori, standard hygienic condition, proper diet, and improved living standards. One of the most common and complicated factors of gastric cancer is infection with Pylori. The main intention of this article is to elaborate the concerned review of GC and up-to-date information about its occurrence moreover its risk aspects in Pakistan.